Impact of the Symbol in the Formation of the Poetic Imagery: (Daik Al-Jin poetry 161-236 AH- a model) - Khudhair, Muhammad Saib (Al-Adab Journal, 2020)
The poet depicts an image with words, when the words come in a sequence they represent a poetic imagery of a great amount of artistry and creativity. Daik Al-Jin used a lot of these images in his poetry. The reader notices that the symbol has an important role in the formation of the imagery, and many types of imageries appeared such as the elegy image and the flirtatious image. Among the symbols employed by Daik Al-Jin is the symbol of the antelope, the symbol of the rooster and the symbol of the grave. Various poetic imageries appeared including the winery image which adds for winery a sense, feelings, and clear effects for its drinker as if it were a way to escape from the real world to the fantasy world. In his poetry, a complete imagery appears in a single poem starting from the first verse and ends with its end, which makes it clearly visible.